2022
DOI: 10.3390/molecules27103325
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activity of Organic Extracts of Solidago graminifolia and Its Main Metabolites (Quercetin and Chlorogenic Acid) against Spodoptera frugiperda: An In Vitro and In Silico Approach

Abstract: Spodoptera frugiperda (S. frugiperda) remains a global primary pest of maize. Therefore, new options to combat this pest are necessary. In this study, the insecticidal activity of three crude foliar extracts (ethanol, dichloromethane, and hexane) and their main secondary metabolites (quercetin and chlorogenic acid) of the species Solidago graminifolia (S. graminifolia) by ingestion bioassays against S. frugiperda larvae was analyzed. Additionally, the extracts were phytochemically elucidated by ultra-performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…In addition, the SMAL extract was distinguished by derivatives of quercetin, in which it attained a good affinity on the active site of acetylcholinesterase but with a lower binding energy compared to chlorpyrifos against insect pests of the Hemiptera, Diptera, and Lepidoptera. On the contrary, quercetin was almost safe for natural enemies of Coleoptera and pollinators of Hymenoptera [54,55]. Moreover, the SMAL extract in this study featured derivatives of caffeic acid.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, the SMAL extract was distinguished by derivatives of quercetin, in which it attained a good affinity on the active site of acetylcholinesterase but with a lower binding energy compared to chlorpyrifos against insect pests of the Hemiptera, Diptera, and Lepidoptera. On the contrary, quercetin was almost safe for natural enemies of Coleoptera and pollinators of Hymenoptera [54,55]. Moreover, the SMAL extract in this study featured derivatives of caffeic acid.…”
Section: Discussionmentioning
confidence: 55%
“…Sequential binding of multiple molecules of caffeic acid was shown to possess a potent inhibitor of Helicoverpa armigera Hubner gut proteases' activity and gene expression [56]. Ultimately, some of the moieties of the SMAL extract might share only a synergistic action, for instance, the synergistic effects of the derivatives of chlorogenic acid on quercetin [55], vanillin mixtures with imidacloprid or α-cypermethrin [57], and daidzein on the baculovirus biopesticide [58]. Moreover, the hesperidin-Mg complex was found to be a trigger for the insecticide's potential against the adults of Bemisia tabaci Gennadius and Spodoptera frugiperda (J.E.…”
Section: Discussionmentioning
confidence: 99%
“…It must be remembered that, despite being of the same genus, the species are different, which could explain the greater activity observed in this study. In the same sense, Herrera-Mayorga et al [47] evaluated the insecticidal activity of some flavonoids (e.g., quercetin), as well as some phenolic acids (e.g., chlorogenic acid), against S. frugiperda larvae, and they found that quercetin had a mean lethal concentration (LC 50 ) of 157 ppm, lower than that presented in this study (525 ppm). Likewise, Herrera-Mayorga et al [47] evaluated a 1:1 mixture of quercetin with chlorogenic acid, which presented an LC 50 of 729 ppm-higher than that obtained in this research.…”
Section: Evaluation Of the Insecticidal Activity Of Kaempferol Agains...mentioning
confidence: 54%
“…The insecticidal activity against Spodoptera frugiperda was evaluated according to a previous method. The compounds (10 mg/mL) in DMSO were prepared and further diluted with distilled water containing 1‰ Tween-80 to the concentrations of 62.5, 125, 250, and 500 μg/mL. The fresh corn leaf disks (5 mm × 5 mm) were soaked in the solution of the test reagent 3–5 times.…”
Section: Methodsmentioning
confidence: 99%